Government policy interventions to reduce veterinary antimicrobial consumption in production animals: a protocol for a systematic review and evidence map - Kayla Strong; Fiona Emdin; Sam Orubu; Susan Rogers Van Katwyk; Heather Ganshorn; Jeremy Grimshaw; Mathieu J. P. Poirier (Systematic Reviews)
Abstract Background Globally, agricultural production systems consume two-thirds of all antimicrobials. These systems are used to raise animals that produce products for consumption, such as meat, eggs, milk, and wool. The World Bank estimates that by 2030, AMR will reduce global livestock production by up to 7.5%, resulting in economic losses of up to one trillion USD. Governments worldwide have implemented various policies to promote antimicrobial stewardship in production animals, such as requiring veterinary prescriptions for antimicrobial use, restricting certain antimicrobials, and prohibiting antimicrobial use for growth promotion. However, the efficacy of these measures remains uncertain, necessitating a comprehensive review to guide policymakers. This review will identify and describe implemented government policy interventions to reduce veterinary AMU and AMR in production animals. A secondary analysis will map the policy pathways and the stakeholders involved in their successful implementation. Methods An electronic search strategy has been developed in consultation with a public health librarian and a veterinary health librarian. CAB Abstracts, MEDLINE, Web of Science, and ProQuest Dissertations will be searched, and additional studies will be identified using gray literature searches. The intervention of interest is any policy intervention enacted by a government or government agency in any country to change antimicrobial use in production animals. For inclusion within the review, studies must (1) describe the government policy, (2) quantitatively measure the impact of the policy in production animals using a rigorous study design, and (3) measure the impact of the intervention through antimicrobial use (AMU) or AMR. Two independent reviewers will screen for eligibility using defined criteria, and data will be extracted using Covidence software and Excel, respectively. Results will be synthesized narratively and visually (using maps and Sankey plots) to identify evidence gaps. Discussion This systematic review is intended to inform future government policies addressing antimicrobial resistance and antimicrobial use in production animal systems. It will also inform future research priorities by identifying evidence gaps about the effectiveness of various policy interventions. Systematic review registration Open Science framework.